Verification of Vehicular Emitted Aerosol Components in Soil Biochemical Characteristics in Owerri West Local Government Area, Imo State, Nigeria - Ubuoh Emmanuel Attah (Institute of Advanced Engineering and Science, 2012)
The study was carried out in Avu Junction in Owerri West L.G.A. at graded distant from the tarred road with an average vehicular flow between 10,000 to 12,000 per day. Soil samples were taken at the distant of 50m, 100m, 150m and 200m respectively. And auger soil samples were taken at the depths of 0-30 cm and 30-45 cm accordingly. Soil factor, heavy metals and microbial populations were investigated at graded distances. From the result of soil factors, pH values indicated acidity with decreased distant from the tarred road ranging between 4.52 – 6.32, soil temperature on the topsoil was higher than subsoil ranging between 19- 25 0C and 18 – 22 0C and soil moisture increases with increased distant from the tarred road ranging between 10.00 – 13.3. Heavy metal concentrations in the soil increased with decreased distant in the order of Pb < Zn < Ni < Cu < Cd. Overall results revealed that Cd in the soil constitutes the highest percentage of 91.7%, Ni 90.9%, Cu 90.1%, Pb. 84.7% and Zn. 81.7%. Significantly, higher fungi and bacterial populations were recorded at increased distant from the tarred road. This then called for proactive measures to checkmate soil contamination due to pollutants from vehicular flows.